Caracterização biológica da ictiofauna carnívora da Represa do Beija-Flor, Estação Ecológica de Jataí, Luiz Antônio, SP - Fernandes, Daniela (Universidade Federal de São Carlos, 2010)
This study was done in Beija-flor Dam a reservoir built in 1965 by damming the Beijaflor stream , a tributary of the Mogi-Guaçu river. It is deemed to be flooded lake to maintain constant communication with the river and stream Sunbird and there is no mechanism to control the entry and exit of water into the system. It is believed that the dam acts as a rest area and can feed and reproduce for migratory species that go up the Mogi-Guaçu river, as well as ponds. Therefore the study of feeding and reproduction of carnivorous fish that area, which as top predators can alter the ecology and evolution of prey populations, play an important, to the knowledge of the biology of the species in particular, and to understand the interactions of a fish assemblage and can therefore be used as a tool in the development of management strategies. To this end the present study consists of two chapters, the first addressing the population structure, reproductive aspects and feeding of the species Serrasalmus maculatus and the second, with an analysis of food, overlap and similarity between the diets of carnivorous species of Beija-flor Dam.
Keywords: Ecologia; Dinâmica da população; Carnívoro; Peixes - alimentação; Reprodução; CIENCIAS BIOLOGICAS::ECOLOGIA